Calidad del servicio de agua potable en las comunidades rurales de la Provincia de Chimborazo - Paca Rivadeneira, Johanna Vanessa (2021)
A fundamental right that all human beings have is access to quality essential services that satisfy the basic needs of each individual. Among them, the drinking water service turns out to be essential due to its impact on health and quality of life. The program developed by the National Government called "Agua Segura y Saneamiento para Todos" mentions that access to drinking water service is the primary resource for population development. However, according to several studies carried out in the country, a large part of the Ecuadorian population, especially the rural ones, lacks quality drinking water service. In the province of Chimborazo, the Ministry of Ambiente, Agua y Transición Ecológica (MAATE), registers 284 drinking water systems that have legal status, the vast majority of which have shortcomings either in pressure, coverage, maintenance; attributing to the fact that the quality of the service is not adequate. For this reason, the main objective of the following research is to evaluate the quality of drinking water services in rural communities in the province. Six parameters were analyzed (organoleptic quality, quantity, continuity, pressure, coverage, damage to infrastructure, and tariff). These allowed us to determine that the quality of the drinking water service in the Province of Chimborazo is acceptable from the users' perception